Rancang Bangun Sistem Informasi Penerimaan Peserta Didik Baru (PPDB) di Dinas Pendidikan Provinsi Jambi - Fidela, Talitha Marsha; Saputra, Hendra; Asyifa, Nurdillah Laina; Pratama, Rizky; Asyrovi, Sabil; Oktavia, Rima; Afifah, Seftia Nur; Munawaroh, Kholifah Nur; Putri, Utami Mizani (Universitas Multi Data Palembang, 2024)
In a modern era characterized by advances in information and computer technology, education faces the challenge of presenting information effectively to meet diverse needs. The role of information and computer technology in the school admission process is becoming increasingly important. The Jambi provincial education office has a crucial responsibility in ensuring an equitable quality of education in its region. However, obstacles arise when the implementation of the online New Learner Admission (PPDB) system has not been evenly distributed across all SMA/SMK in Jambi Province, especially in district areas and new schools. To overcome this problem, developing a web-based PPDB application using the PHP language and MySQL web server is the right choice. The aim is to improve accessibility, transparency, and quality in the implementation of PPDB in the Jambi Province area. The web technology chosen allows this application to be accessed easily from various devices with an internet connection, without requiring the installation of additional software. Thus, the development of this PPDB application is expected to provide an effective and efficient solution in the process of admitting new students in Jambi Province.